Strategi Pengembangan Bisnis dan Penyusunan Laporan Keuangan Sederhana sebagai Wujud Gerakan Nasional Revolusi Mental (GNRM) bagi Para UMKM Batik di Kota Solo - Rosa Fitriana (LPPM UNINUS, 2022)
The perpetrators of batik SMEs in Solo should have tips to optimize opportunities in achieving their goals, namely by having a business development strategy and understanding the importance of preparing financial statements. The methods used in the implementation of the service are mentoring and training using technical information presentation and simulation methods as well as mentoring with an approach to providing training and lectures for batik craftsmen through online and offline methods. The implementation of the service was carried out on September 25, 2020. From the results of this activity, all participants who were batik SMEs responded very well and understood the material presented related to business development strategies and the preparation of simple financial reports. Positive changes can be seen after carrying out this activity, the participants who are batik SMEs, initially did not have a strategy that was reliable enough in developing their business and also had not prepared financial reports, started trying to be able to have a business development strategy and tried to compile financial reports. This activity is of course expected to create a condition that supports government programs on how people can implement the National Movement for Mental Revolution (GNRM) in the economic field.